Auditing / Theory and Practice: Second Edition - Dunn John (Prentice Hall, 1996)
This book provides a balanced and pertinent framework for the study of auditing. Preface, Abbreviations, The Regulatory Framework of Auditing, Why Have an Audit?, Auditor Independence, The Auditor's Duties, International Comparisons, Audit Reporting, The Audit Report, Qualified Audit Reports, The Collection of Evidence, The Conduct of an Audit, Audit Evidence and Testing, Internal Control, Computer Audit, Audit Sampling, The Sales Cycle, The Purchases Cycle, Audit of the Balance Sheet, Other Roles for Audit, Internal Audit, Management Auditing, Environmental Audit, Appendix: Proposed Structure of Statements of Auditing Standards, Index.